1990
DOI: 10.1111/j.1440-1681.1990.tb01367.x
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERISTICS OF CARDIOVASCULAR REFLEXES ORIGINATING FROM 5‐HT3 RECEPTORS IN THE HEART AND LUNGS OF UNANAESTHETIZED RABBITS

Abstract: 1. When phenylbiguanide (1-PBG) (6.25-400 micrograms) was injected into the left atrium, right atrium or pulmonary artery of unanesthetized rabbits it caused dose-dependent falls of heart rate and arterial pressure, and short-lived hypopnoea or apnoea. The threshold dose was 50-100 micrograms. Maximal falls of heart rate (86-108 beats/min) and arterial pressure (33-35 mmHg) occurred at a dose of 200 micrograms. The latency between injection and onset of the bradycardia was 2.2-2.6 s and did not depend on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 40 publications
(58 reference statements)
3
37
0
Order By: Relevance
“…Numerous reports have appeared in the literature, describing the cardiovascular reflexes [1][2][3][4][5][6], agonists and antagonists [3][4][5][6][7][8][9], visceral reflexes [10,11], and physiological [12] activity, as well as industrial [13][14][15][16][17] applications of arylbiguanides. Our long-term interest in chemical reactions induced by charge-transfer complexation forms a part of our systematic efforts to obtain new heterocyclic systems [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have appeared in the literature, describing the cardiovascular reflexes [1][2][3][4][5][6], agonists and antagonists [3][4][5][6][7][8][9], visceral reflexes [10,11], and physiological [12] activity, as well as industrial [13][14][15][16][17] applications of arylbiguanides. Our long-term interest in chemical reactions induced by charge-transfer complexation forms a part of our systematic efforts to obtain new heterocyclic systems [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In rabbits (Evans et al, 1990a) and rats (Willette et al, 1982) phenylbiguanide-sensitive cardiopulmonary afferents are prominent, whereas they appear to be absent in dogs (Dawes et al, 1952) and man (Jain et al, 1972). On the basis of these pieces of circumstantial evidence we had expected to find that in conscious rabbits the signal that initiates the sympathoinhibitory phase of simulated haemorrhage was conveyed by phenylbiguanide-sensitive cardiac afferents, but we have not been able to demonstrate that this is so.…”
Section: And T A|mentioning
confidence: 74%
“…The effect of phenylbiguanide is mediated by pharmacologically-specific 5-HT3 receptors (Wright & Angus, 1988;Evans et al, 1990a). The afferents run mainly, though not exclusively, in the vagus nerves.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have examined the mechanism of 5-HT-induced BJR. Evans et al (10) reported that intraatrial injection of phenylbiguanide, a 5-HT3-receptor agonist, induced a dose-dependent decrease in heart rate in conscious rabbits and that this response was inhibited by atropine and bilateral vagotomy. Bradycardia induced by intraatrial and intraventricular injections of 5-HT was also inhibited by both atropine and vagotomy in conscious and anesthetized dogs (8).…”
Section: Bjr Induced By 5-ht Injected Into the Left Ventriclementioning
confidence: 99%
“…Bolus intravenous injection of 5-HT causes transient bradycardia (the von Bezold-Jarisch reflex; BJR) in many species including rats, cats, dogs and rabbits (8)(9)(10)(11). Fozard (12) reported that this reflex in anesthetized rats is mediated through the activation of 5-HT3 receptors located on endings of vagal afferent nerves.…”
mentioning
confidence: 99%